R&D-based growth in the post-modern era - Holger Strulik; Klaus Prettner; Alexia Prskawetz (Vienna University of Technology, Institute of Mathematical Methods in Economics, Research Group Economics, 2011)
Conventional R&D-based growth theory suggests that productivity growth is positively correlated with population size or population growth, an implication which is hard to see in the data. Here we integrate R&D-based growth into a unified growth setup with micro-founded fertility and schooling behavior. We then show how a Beckerian child quality-quantity trade-off explains why higher growth of productivity and income per capita are associated with lower population growth. The medium-run prospects for future economic growth - when fertility is going to be below replacement level in virtually all developed countries - are thus much better than predicted by conventional R&D-based growth theory.
Keywords: J13; J24; O10; O30; O40; 330; R&D; unified growth theory; declining population; fertility; schooling; human capital; post-modern society